The assessment of the quality and content of YouTube videos concerning dental treatments performed under general anesthesia (Annals of Medical Research, 2023)
Aim: This study evaluates the content and quality of YouTube videos on dental procedures under general anesthesia, a crucial topic for patients with disabilities or complex medical conditions.Materials and Methods: A cross-sectional analysis was conducted on the first 200 videos yielded by a "general anesthesia in dentistry" search on YouTube. Videos were evaluated based on 13 criteriaand Video Information and Quality Index (VIQI) was used for overall quality assessment.Results: The study analyzed 180 videos, with 115 meeting the selection criteria. These videos showed good reliability in content and Video Information and Quality Index (VIQI) scores, and were mostly uploaded by healthcare professionals from the U.S., India. Average video length was about 7 minutes. They mainly discussed reasons for choosing general anesthesia. Majority of videos (79.1%) were uploaded by healthcare professionals. Among the 115 videos, 20% were full-content, while 83.5% and 16.5% were classified as high-content and low-content, respectively. High-content videos were longer and had higher VIQI scores.Conclusion: Majority of videos on the topic were created by professionals. The reasons for choosing general anesthesia were the most discussed topic. Despite study limitations, these YouTube videos serve as effective supplementary material for both healthcare professionals and laypersons.
Keywords: General anesthesia; Dental treatments; YouTube; VIQI